Brownfields : - Rafson, Harold J. (McGraw-Hill, 1999)
This ready-to-use, how-to manual--edited by active developers who have bought, remediated, and sold brownfields--gives you a commanding look at one of today's leading environmental issues. Filled with the latest hands-on tools, Harold and Robert Rafson's step-by-step book simplifies the task of removing the barriers to redevelopment that plague environmentally distressed properties. Brownfields goes beyond the legal and technical issues that preoccupy other current books, to focus on all the critical aspects of putting together a successful brownfields project--mortgages, marketing, and more. Complete with case studies drawn from the authors' own experience, this guide is required reading not just for owners or developers, but for every stakeholder--from environmental regulators, to bankers, realtors and prospective buyers.